DOES COOPERATIVE MEMBERSHIP IMPROVE COCOA FARMER INCOME? EVIDENCE FROM MANKRANSO COCOA DISTRICT, GHANA - Felix Nketia Boadu; Patrick Appiah; Enoch Kwame Tham-Agyekum; John-Eudes Andivi Bakang; Fred Nimoh (Agricultural Socio-Economics Journal, 2023)
This study investigates whether cocoa cooperatives can significantly improve the revenue of cocoa farmers. A simple random sampling technique was adopted to draw a sample of 306 farmers from a population of 25,109 cocoa farmers in the Mankranso Cocoa District. Structured questionnaires were administered to obtain primary data from the households. Descriptive statistics were used to compare revenues generated by cocoa farmers. The study employed the multiple linear regression model to assess the effect of cooperative membership on cocoa farmers’ income. The study also used the Kendall's coefficient of concordance to assess the constraints faced by cooperatives societies. Revenue comparison reveal that although the price per bag of cocoa did not vary, the income level of cooperative members was significantly higher than non-members. Cooperative membership, credit access, and extension service significantly and positively affect cocoa revenue and revenue generated from other activities. The Likert scale analysis also indicate that farmers generally agree that cooperatives play social and production roles but disagree that cooperatives play appropriate financial roles. Lack of external motivation was the main limiting constraint faced by cocoa farmers. The study recommends that extension and credit institutions should be strengthened among cocoa farmers. Importantly, the positive effect of cooperative membership raises the need to incentivize cocoa cooperatives and the need for farmers to be actively motivated to join cooperative societies.